2021
DOI: 10.3389/fimmu.2021.731807
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Function of Interferon-Lambda (IFNλ) and Its Receptor in Asthma

Abstract: Asthma is a chronic respiratory disease affecting people of all ages, especially children, worldwide. Origins of asthma are suggested to be placed in early life with heterogeneous clinical presentation, severity and pathophysiology. Exacerbations of asthma disease can be triggered by many factors, including viral respiratory tract infections. Rhinovirus (RV) induced respiratory infections are the predominant cause of the common cold and also play a crucial role in asthma development and exacerbations. Rhinovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 129 publications
1
14
0
Order By: Relevance
“…Previous studies have showed that type-III interferon response was strongly induced by respiratory viruses in nasal epithelial cells [37] highlighting that an impairment of this response might contribute to the defective antiviral response in asthma. However in the context of asthma, major differences were observed between in vivo studies and in vitro studies performed in isolated bronchial epithelial cells: with most in vivo studies showing an antiviral IFNλ induction in asthma, while, similarly to our own results, majority of the in vitro studies report a defect of IFNλ [38]. The current increase of studies on the type-III interferon response to respiratory viruses should unveil in the coming years the potential benefic effect of altering the IFNλ response and impact on patients.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have showed that type-III interferon response was strongly induced by respiratory viruses in nasal epithelial cells [37] highlighting that an impairment of this response might contribute to the defective antiviral response in asthma. However in the context of asthma, major differences were observed between in vivo studies and in vitro studies performed in isolated bronchial epithelial cells: with most in vivo studies showing an antiviral IFNλ induction in asthma, while, similarly to our own results, majority of the in vitro studies report a defect of IFNλ [38]. The current increase of studies on the type-III interferon response to respiratory viruses should unveil in the coming years the potential benefic effect of altering the IFNλ response and impact on patients.…”
Section: Discussionsupporting
confidence: 74%
“…TLR7 can induce the expression of IFN- γ , decrease the proportion of Th2 cells, enhance Th1/Treg responses to aeroallergens, and reduce proeosinophil aggregation and chemokine and IgE synthesis [ 78 , 79 ]. The activation of TLR7/8 can enhance IFN λ receptor expression and reduce the airway inflammatory response [ 80 ]. In this study, we measured the levels of IL-4, IL-17, IFN- γ , and IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that asthma exacerbation after RV infection is in part related to a deficient IFN-response which, in turn, leads to T2-inflammation (Duerr et al, 2016). Nevertheless, many studies, particularly in adult populations, did not observe such a deficient IFN-response, or even found an increased response (Krammer et al, 2021;Yang et al, 2021;Jackson and Gern, 2022;Liew et al, 2022). These inconsistent observations may rely on the baseline level of asthma control and severity between studies, the population age, the model used, and/or the experimental settings.…”
Section: Discussionmentioning
confidence: 99%